THE EFFECT OF FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, AND SALES GROWTH ON COMPANY VALUE IN THE NON-CYCLICAL CONSUMER SECTOR ON THE INDONESIA STOCK EXCHANGE - Citra Tionar Simanjuntak; Meily Surianti; Khanti Listya; Raya Puspita Sari Hasibuan (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This research seeks to empirically examine the effects of free cash flow, investment opportunity set, and sales growth on company value within the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX). Employing a purposive sampling method, the study analyzes a sample of 75 companies over five years (2019–2023), yielding a total of 375 observations. Data were collected through documentation, specifically from annual reports and audited financial statements of the selected companies, accessible via the official IDX website and the respective companies’ websites. The dataset was analyzed using panel data regression techniques implemented in EViews version 13. Findings reveal that free cash flow (FCF) does not have a statistically significant effect on company value, whereas the investment opportunity set (IOS) positively influences company value. Conversely, sales growth is found to harm company value